Italian teachers’ beliefs on covariational reasoning: an exploratory study - Taranto, Eugenia; Bagossi , Sara; Ferretti, Federica; Arzarello, Ferdinando (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Covariational reasoning is the ability to grasp relationships between quantities and express them mathematically. Despite the recognized relevance of its understanding and knowledge, research shows that few students and teachers are able to adopt covariational reasoning. Our study aimed to investigate whether Italian teachers are aware of covariational reasoning and how and in what way it is present in Italian teaching practices. A teacher professional development course on the topic was launched, and questionnaires were administered at the beginning and end of the course. Teachers’ views and beliefs about covariation and the possible changes regarding them after their participation in the course are investigated. The first analyses carried out on this data and initial reflections on the topic are shared.